Utilization of Hydro Vortex Energy In Watershed Conservation Efforts and Increasing Community Nutrition Through The Fisheries Sector and Educational Tourism In Songgon - Yeddid Yonatan Eka Darma; Winardi Sani; Agung Fauzi Hanafi; Adetiya Prananda Putra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The residents of Songgon District, who are generally farmers, make rice fields and plantations dominant in the community's economy. Once a year durian trees can be harvested and once a rice harvest, this makes agriculture and plantations the backbone of the source of life for Songgon District, which results in the villagers' income being only annual. So that the economic sector that is able to generate income for villagers both on a monthly and daily basis, such as in the fisheries and tourism sectors, needs special attention for the development of the rural economy, given the huge potential possessed by Songgon District. Garbage is a major problem in this place, for example on the banks of the Binau river which is located in Songgon Village/District, opposite the Songgon District Office to be exact, which used to be full of piles of garbage. Residents around are reluctant to pass or do activities around the watershed (DAS). Therefore we are here with Pertamina Muda present in the development of the river fisheries sector such as controlled fish stocking (pioneered by Mr. Wibi Untoro) in the Binau river flow path and by utilizing Hydro Vortex Energy is a solution that can be implemented because it is proven to improve the community's economy and public awareness of the environment.